“Evaluación de la selectividad de herbicidas postemergentes, interaccionados con distancias de siembra en el cultivo de Maíz (Zea mays L.) en la zona de Puebloviejo”. - Mina Coello, Marioly Alexandra (2019)
VIII. SUMMARY The present experimental work was carried out in the lands of Mr. Wilson Enrique Camacho Vera, located in Via Ventanas - Puebloviejo, "Josefa" site, belonging to the Puebloviejo canton. The geographical coordinates are 110597.97 UTM south latitude and 277438.26 UTM west longitude and 8 msnm. The area has a humid tropical climate, with an average annual temperature of 25.40 ° C, annual precipitation of 2048.00 mm, average evaporation of 1132.90 mm, relative humidity 79% and 725.10 hours of annual heliophany. The soil is flat topography, clay loam texture and regular drainage. The corn hybrid was used as planting material. The treatments studied were herbicide products and doses (Dublon gold in doses of 50 and 70 g / ha, Equiplus 100 and 120 g / ha, Nicosulfuron 32 g / ha + Amine 0, 5 L / ha and control with three manual weeding) and planting distances (20 x 80 and 15 x 90 cm). The experimental design of "Complete random blocks" was used, in factorial arrangement A x B, where the factor A was the herbicidal products, the factor B the planting distances, with 3 replications. To perform the evaluation of treatment averages, the Tukey test was used at 95% probability. For the execution of the trial, all the practices and agricultural work that the crop requires for its normal development were carried out, such as land preparation, sowing, weed control, phytosanitary control, fertilization, irrigation and harvesting. For the results obtained it was determined that the applied herbicidal products did not cause toxicity in the cultivation of corn, Copa hybrid; the best weed control was observed in the use of Equiplus in doses of 100 g / ha planted at a distance of 15 x 90 cm; the variable days to flowering interacted with the planting distances did not report significant differences; the agronomic characteristics of height of plant, height of insertion of the ear, diameter and length of ear, grains per ear and weight of 1000 grains, reflected better results with the use of Equiplus in doses of 100 g / ha sown at a distance of 15 x 90 cm and the highest yield of the crop and net benefit was presented with the application of Equiplus in a dose of 100 g / ha sown at a distance of 15 x 90 cm with 6552.5 kg / ha and $ 264.0. Keywords: selectivity, herbicides, planting distances, corn.